The Mechanical Behavior of Bone Cement in THR in the Presence of Cavities - Benouis, A.; Serier, B.; Bachir Bouiadjra, B. (Engineering, Technology & Applied Science Research, 2014)
In this work we analyze three-dimensionally using the finite element method, the level and the Von Mises stress equivalent distribution induced around a cavity and between two cavities located in the proximal and distal bone cement polymethylmethacrylate (PMMA). The effects of the position around two main axes (vertical and horizontal) of the cavity with respect to these axes, of the cavity - cavity interdistance and of the type of loading (static) on the mechanical behavior of cement orthopedic are highlighted. We show that the breaking strain of the cement is largely taken when the cement in its proximal-lateral part contains cavities very close adjacent to each other. This work highlights not only the effect of the density of cavities, in our case simulated by cavity-cavity interdistance, but also the nature of the activity of the patient (patient standing corresponding to static efforts) on the mechanical behavior of cement.